A Pluralistic Approach to Protected Area Governance: Indigenous Peoples and Makuira National Park, Colombia - Premauer, Julia Margareta; Berkes, Fikret (Ethnobiology and Conservation, 2015)
Based on a study of collaborative governance (Spanish cogobierno, literally co-government) in Makuira National Park overlapping with an Indigenous collective territory of the Wayúu people recognised by the Government of Colombia, we analyse how Indigenous rights and conservation interests are negotiated between the national parks authority and local Indigenous governing authorities. Recognised common interests provide a basis for collaboration in protected area governance even where conflicting interests exist. The arrangements arrived at by negotiation incorporate Indigenous commons governance and parks conservation objectives, enabling territorial use planning which allows for both conflict management and protected area management. Ongoing collaborative governance based on common interests, brings both benefits and tradeoffs. The Wayúu give up part of their self-determination rights and the Park gives up part of the ideals of ecosystem conservation based on biological criteria. The strategic alliance works because it is based on the recognition of the legitimacy of Indigenous governing authority, the Parks’ role in protecting Wayúu territory, and the complementary strengths of the two parties. The core message of the case is that designing an inclusive and broad practice of conservation requires an approach involving processes that acknowledge common interests and tradeoffs for both parties.